Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Microbial Biotechnology: Energy and Environment 2012
DOI: 10.1079/9781845939564.0250
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of petroleum hydrocarbons in contaminated soil.

Abstract: This chapter provides a clear insight into microbial degradation of petroleum hydrocarbons in contaminated soil that have emerged from the growing body of bioremediation research and its applications in practice. Understanding the biodegradability of several classes of petroleum contaminants is of critical importance for developing bioremediation strategies for risk mitigation. In situ (biostimulation, bioaugmentation, phytoremediation) and ex situ (biopiling, bioreactors, composting, land farming, ) bioremedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…In spite of these advantageous potentials of bioremediation usage, problem persists from the consideration that contaminating pollutant removal efficiencies from different biological species or organisms that could be used for bioremediation are highly variable [10,[15][16]. Also, while studies have proposed the use of fungi species, including Aspergillus spp., among useful microorganisms for oil polluted soil bioremediation [2, [11][12]15,18] no dataset exists on Aspergillus niger usage for bioremediation of raw and treated crude oil polluted soil. Additionally, while reported works employ bacteria strains, Enterobacter cloacae and Burkholderia cepaciam [11], or activated carbon from coconut shell [16] for remediating Nigerian Escravos Light…”
Section: Comprehensive Dataset Of Biologically-mediated Remediation Omentioning
confidence: 99%
“…In spite of these advantageous potentials of bioremediation usage, problem persists from the consideration that contaminating pollutant removal efficiencies from different biological species or organisms that could be used for bioremediation are highly variable [10,[15][16]. Also, while studies have proposed the use of fungi species, including Aspergillus spp., among useful microorganisms for oil polluted soil bioremediation [2, [11][12]15,18] no dataset exists on Aspergillus niger usage for bioremediation of raw and treated crude oil polluted soil. Additionally, while reported works employ bacteria strains, Enterobacter cloacae and Burkholderia cepaciam [11], or activated carbon from coconut shell [16] for remediating Nigerian Escravos Light…”
Section: Comprehensive Dataset Of Biologically-mediated Remediation Omentioning
confidence: 99%
“…According to Ite et al [5], the inadvertent discharges of petroleum hydrocarbons and chemical-derived waste streams associated with petroleum exploration and production have caused environmental pollution, adverse environmental and/or human health problems, negative impacts on the terrestrial ecosystems, detrimental impacts on regional economy, socio-economic problems and degradation of oil producing host communities in the Niger Delta region. Some of the consequences associated with the inadvertent release of petroleum hydrocarbons into the environment are as follows: (i) atmospheric pollution associated with natural gas flaring and venting which may contribute to global climate change [4,11,12]; (ii) pollution of marine ecosystem which may result in adverse impacts on wildlife and negative impact on tourism, fishing and other related businesses; (iii) pollution of soil and controlled water sources (surface and ground water) [1,7,8,[13][14][15][16][17], (iv) socio-economic problems and deterioration of our cultural heritage items in the impacted oil producing host communities in the region [1,5,6,18,19,20,21], and (v) contaminated land, food quality issues and reduction in agricultural produce [8,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the Niger Delta region is plagued with petroleum hydrocarbons contamination and the region has been rated as one of the most crude oil spill vulnerable areas in the world [28]. It is widely known that environmental contamination, human health risks, and negative socio-economic consequences of most petroleum hydrocarbons pollution in the world depend on the intersection of the event, the geographic setting, the characteristics of the regional population, corporate governance systems and political economy [1,5,6,27]. Over the past fifty-five years, it has been reported that an estimated 10 m to 13 m tons of petroleum hydrocarbons have been spilled into the Niger Delta regions and about 77 % of spilled petroleum hydrocarbons have not been recovered [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations